2020
DOI: 10.1038/s41598-019-57103-5
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies neutralizing diphtheria toxin in vitro and in vivo

Abstract: Diphtheria is an infectious disease caused by Corynebacterium diphtheriae. the bacterium primarily infects the throat and upper airways and the produced diphtheria toxin (Dt), which binds to the elongation factor 2 and blocks protein synthesis, can spread through the bloodstream and affect organs, such as the heart and kidneys. For more than 125 years, the therapy against diphtheria has been based on polyclonal horse sera directed against Dt (diphtheria antitoxin; DAt). Animal sera have many disadvantages incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 80 publications
3
50
1
3
Order By: Relevance
“…Even though ORFeome also has been reported to allow epitope mapping in the case of a hybridoma-derived monoclonal antibody with considerably high resolution 31 , the results from the present study indicate that single-gene display can significantly improve the resolution of the detected epitope region. This corroborates with the fact that most of the antibodies mapped against diphtheria toxin using a similar procedure had relatively short MSR (14–38 amino acids) 59 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Even though ORFeome also has been reported to allow epitope mapping in the case of a hybridoma-derived monoclonal antibody with considerably high resolution 31 , the results from the present study indicate that single-gene display can significantly improve the resolution of the detected epitope region. This corroborates with the fact that most of the antibodies mapped against diphtheria toxin using a similar procedure had relatively short MSR (14–38 amino acids) 59 .…”
Section: Discussionsupporting
confidence: 82%
“…After performing the MSR analysis using single-gene phage display, most of the antibodies showed MSR length ranging from 71 and 87 amino acids, referring to the approximate size of one of the LD of PDC-E2. This indicates that the correct folding of these domains is essential for recognition by the selected antibodies, an observation that was also noticed in a previous study with diphtheria toxin, where the MSR of the C-domain had ≈ 150 amino acids 59 . Single-gene panning also showed that GSM133-A4 actually recognized both LD of the target, and made it possible to determine the MSR of GSM134-C1, which showed no result with ORFeome display.…”
Section: Discussionsupporting
confidence: 81%
“…Antibody combinations can have a synergistic effect as previously described for toxins and viruses 32,[52][53][54] . This approach may also avoid formation of viral escape mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble antibody fragments (scFv) were produced in 96-well polypropylene MTPs (U96 PP, Greiner Bio-One) as described before 54,66 For the ELISA, 100 ng of antigen was coated on 96 well microtiter plates (High binding, Greiner) in PBS (pH 7.4) overnight at 4°C. After coating, the wells were blocked with 2% MPBST for 1 h at RT, followed by three washing steps with H2O and 0.05% Tween20.…”
Section: Screening Of Monoclonal Recombinant Binders Using E Coli Scmentioning
confidence: 99%
“…An immune antibody library for Pseudomonas aeruginosa was reported to generate neutralizing antibodies targeting the Psl exopolysaccharide [56]. A recent report highlighted the development of neutralizing diphtheria antibodies from an immune library [57]. Raxibacumab, obiltoxaximab and bezlotixumab are exotoxins neutralizing antibodies approved by FDA for treatment of bacterial infections.…”
Section: Bacterial Infectionsmentioning
confidence: 99%